A novel hybrid solar-biomass design for green off-grid cold production, techno-economic analysis and optimization. (April 2021) - Behzadi, Amirmohammad; Arabkoohsar, Ahmad; Sadi, Meisam; Chakravarty, Krishna Hara
Highlights: A novel design of solar collector combined with biomass-firing heaters is proposed. Comparative transient modeling is performed to find the best configuration. Multi-objective optimization is applied to the best configuration. The optimum domain of major variables is determined through scatter distribution. The optimum cost and emission of 47.1 /MWh and 440.62 kg/MWh is obtained. Abstract: This work proposes a novel hybrid renewable-based cold production system consisting of an innovative yet simple design of evacuated solar collectors integrated with a biomass heater, thermal storage tanks, and an absorption machine. The optimal design, sizing of the components, and operating conditions of the hybrid system are investigated via thorough techno-economic modeling and dual-objective optimizations for a case study in India. In addition, the assessments cover different designs of biomass heaters and various biomass types. Finally, using the coefficient of performance (COP), the levelized cost of cooling (LCOC), and the emission index as the prioritization parameters, the most efficient, the most cost-effective, and the most environmentally-friendly configurations are indicated. The results show that integrating evacuated plate collectors with a specific design of biomass-heater burning sugarcane baggas is the most appropriate option from all aspects. According to the optimization results, at the best solution point, emission index and LCOC are, respectively, 440.62 kg/MWh and 47.1 USD/MWh. Moreover, the scatter distribution of major decision parameters indicates that while the volume of the hot storage tank is not a sensitive parameter, the chiller temperature and volume of the cold storage tank should be kept at their lowest bounds.